Forging and sustaining research-minded professionals: teaching undergraduate research through student-community partnerships. - Chakradhar, Kala (Social Work Education, 2018)
The teaching of research is a well-established core component of social work curricula around the world. While educators in social work recognize the value, and need for research they have encountered persistent discomfort and reluctance from students to recognize this need. Practitioners in the field of social work often share this reserve either due to limited self-efficacy with regard to research knowledge and skills or practical constraints. With the growing need for practice-based knowledge, accountability and evidence-based practices to drive outcomes and service effectiveness, it is becoming imperative to not only prepare future social work professionals with the required skill sets but also support current professionals to meet these expectations. This paper showcases a pedagogical endeavor with an undergraduate research course in an American rural university, designed and implemented to create and support research-minded professionals through student-agency research partnerships. Through a collaborative, service-oriented learning, students have gained a new appreciation for research and agency connections while agencies have welcomed the path created to pursue their research agenda. This experience has valuable implications for research capacity building, and for community engaged research empowering future and current professionals to suitably use research toward effective and meaningful service provision.